Methods for producing additively manufactured self-gelling structures and their uses
Patent Information
- Application Number
- JP2023577905
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-06-18
- Filing Date
- 2022-03-18
- Publication Date
- 2025-03-06
AI Technical Summary
Hydrogels used in medical applications face challenges with localization and stability due to ease of movement and tendency to break or disperse under mechanical stress, limiting their effectiveness and requiring on-site preparation, which increases procedure time and error risk.
Development of self-gelling materials and structures with microstructural anchoring properties that allow for localization and stabilization through a 3D printed scaffold, containing a gelling powder that hydrates in situ to form a gel anchored within a porous polymer matrix, maintaining structure and integrating with surrounding tissue.
The self-gelling structures provide improved localization and prolonged residence time within the body, enhancing therapeutic efficacy by anchoring the gel to the polymer mesh network, reducing migration and increasing integration with surrounding tissue.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to the localization and stabilization of hydrogels. [Background technology]
[0002] Hydrogels are useful substrates for medical and other applications, such as tissue healing and regeneration, drug delivery, cell delivery, encapsulation of implantable devices and bioelectronics. Hydrogels are physically similar to the natural matrices that make up the human body, i.e., loose nano-networks containing hydrogen-bonded or electrostatically-bound aqueous media (i.e., most of the human body is gel-like). Due to their physical similarity to biological systems, hydrogels have many medical applications, including but not limited to tissue repair, drug delivery, gene delivery, cell delivery, and reducing inflammation. However, hydrogels for medical use, especially those designed for fixed placement and / or injection in the body, suffer from a number of disadvantages. These disadvantages include: 1) they are difficult to localize (the gels are easily mobile and will delocalize as a result of mechanical stress after implantation), and 2) they tend to break, split, disperse, or disintegrate due to the migration caused by their inability to localize. These technical disadvantages severely limit the effectiveness of medical hydrogels across applications. In addition, hydrogels often must be prepared onsite in an operating room and / or physician's office immediately prior to use, increasing procedure time and costs, and increasing the likelihood of preparation and application errors. Summary of the Invention
[0003] In various embodiments, materials and structures having one or more self-gelling components as defined herein provide improved performance over existing, non-microstructurally anchored gels, for example, because: 1) the microstructurally, i.e., physically, anchored properties help localize the gel and the entire printed or otherwise formed structure, providing the gel with structural form, which allows the gel to be localized and even sutured in place within the body, reducing gel migration, increasing its resistance to mechanical forces, and extending its residence time; and 2) the underlying three-dimensional (3D) printed scaffold (hereinafter referred to as a "3D printed scaffold"), which provides a high degree of localization of the gel and the entire printed or otherwise formed structure, providing a high degree of localization of the gel and the entire structure, which may be localized and even sutured in place within the body, reducing gel migration, increasing its resistance to mechanical forces, and extending its residence time. 1) the engineered macrostructure and unique micro- and nanostructure of the degraded 3D printed scaffold particulate material helps contain and support the gel after implantation or injection; and / or 2) the 3D printed scaffold material containing pre-activated gelling powder is shelf-stable, e.g., can be cut, clipped, compressed, delivered by cannula, etc., prior to hydration, allowing the material to be positioned and hydrated with the surrounding blood, medium, plasma, etc., upon implantation or injection, greatly increasing the device's ability to integrate and heal the surrounding tissue. As used herein, one or more self-gelling components or one or more self-gelling powder components refer to one or more of the same self-gelling components and / or one or more different self-gelling components. Materials with one or more self-gelling components disclosed herein are distinct from injectable hydrogels and implanted 3D printed hydrogels, which are much slower to absorb surrounding biological components because they are already hydrated. Additionally, the underlying nanoporous and microporous polymer meshes in the form of 3D printed constructs (hereinafter referred to as "3D printed constructs") or disassembled 3D printed constructs help maintain the implant morphology or injectable volume, respectively, and improve localization better than polymer or composite meshes that have gel added prior to implantation, where the gel component is not anchored within the nano / microstructure of the polymer network, but instead simply loosely encapsulates the mesh.
[0004] Materials or structures containing gelling powders are disclosed, where the gelling powders are essentially anhydrous and are intended to be gelled after the production or formation of the 3D printed structure and / or after the production of the degraded granules. In other words, the gelling powders are gelled only when activated in a post-processing treatment, as further disclosed below. The gelling powder-containing materials and the underlying matrix, i.e., mesh, structure, expand when hydrated, i.e., gelled, or otherwise activated, as the embedded gelling powder expands and presses against the polymer microporous matrix, i.e., mesh, network. Since the gelling powders are essentially anhydrous, degraded scaffold microgranules containing gelling powders (hereinafter referred to as "degraded scaffold microgranules") can be further obtained by grinding the extruded or otherwise formed material derived from the ink containing gelling powder for further incorporation into a subsequent ink composition, or into degraded scaffold microgranules containing gelling powders (more generally referred to herein as "degraded scaffold gelling granules"). Microgranules are themselves discrete particles composed of discrete particles of gelling powder embedded within a porous biodegradable polymer matrix, in other words degraded scaffold microgranules are composed of a biodegradable polymer matrix with gelling particles embedded in them, granules are understood to be larger than powder particles, degraded gelling granules are microgranules generated from degraded scaffolds that otherwise contain gelling powder.
[0005] The present disclosure also encompasses 3D printed structures having one or more self-gelling components. The 3D printed structures include a porous polymer or polymer composite matrix, i.e., mesh, structure, encapsulating or incorporating dry gelling powder and / or degraded scaffold microgranules (i.e., gelling powder and / or degraded scaffold gelling granules), which is shelf-stable in dry form, and the gelling powder component of the structure is configured to gel when contacted with an aqueous solution. The structure may further include microparticles and / or nanoparticles embedded within the porous polymer matrix, i.e., mesh, structure, in dry form, which become further internally saturated and encapsulated by the gel after the structure is exposed to an aqueous solution. The microparticles and / or nanoparticles may be one or more of a conductive material, a ceramic material, a metallic material, and a biologically derived material. The structure may further additionally include drugs, small molecules, RNA, and / or DNA, and derivatives thereof. The polymer matrix, i.e., mesh, structure, can be a biocompatible polymer matrix, i.e., mesh, structure. The dried gelling powder and / or degraded scaffold microgranules (i.e., gelling powder and / or degraded scaffold gelling granules) are disposed within the porous microstructure of the biocompatible polymer matrix, i.e., mesh, structure. In an example, the 3D printed structure (containing gelling powder and / or degraded scaffold gelling granules) containing dried gelling powder or containing microgranules can be washed with water or washed in an aqueous solution, where the gelling powder undergoes gelation to form a bulky gel and becomes microstructurally, i.e., physically, fixed within the interconnected nanoporous and microporous structures of the porous biocompatible polymer matrix, i.e., mesh, structure. As referred to herein, nanoporosity and microporosity refer to the nature of porosity ranging from nanoscale to microscale. In such examples herein, porosity can be at both nanoscale and microscale. In such examples herein, the porosity may be only on the nanoscale.In such examples herein, the porosity may be only on the microscale. The matrix, i.e., the mesh, structure, and the degraded scaffold gelling granules are highly porous. The pore size of these materials may be, or may be, nanoporous and microporous, as described herein. However, it is noted that the pores of the porous biocompatible polymer matrix are not larger than the degraded scaffold gelling granules themselves. In certain examples, the pore size of the porous biocompatible polymer matrix is 20 μm or less.
[0006] Also described is an ink composition for extrusion-based 3D printing of 3D printed structures having one or more self-gelling powder components. The ink composition includes a solvent-based biocompatible polymer that contains and maintains a dry gelling powder encapsulated or incorporated within the biocompatible polymer, configured to remain storage stable in dry form when washed in alcohol after printing and dried, and to gel when hydrated in an aqueous solution. In an example, the ink composition is not and does not include a hydrogel. In an example, the dry gelling powder has an average particle size of less than 100 μm. In an example, the dry gelling powder component is used in combination with a conductive material, a ceramic material, a metallic material, or a bio-derived material (e.g., proteins, peptides, extracellular matrices, etc.). These other materials may also be in powder form, but may be different or separate from the dry gelling powder, and may be provided in addition to the dry gelling powder. These particles may be microparticles and / or nanoparticles as described above. The microparticles and / or nanoparticles can be any composition that is not soluble in the primary solvent used in the ink, dichloromethane, or the alcohol solution utilized during the wash step. In one example, additional powder components including one or more of nanoscale and microscale materials, which can be one or more of conductive materials, ceramic materials, metallic materials, and bio-derived materials, are suspended in the solvent-based polymer extrudate.
[0007] Also described is a method of forming a structure having one or more self-gelling components, the method comprising: combining the solvent-based polymer with the dried gelling powder to form an ink and extruding the ink to form a structure having an interconnected nano- and microporous polymer matrix, i.e., a mesh, with the gelling powder embedded therein; washing the structure having the nano- and microporous polymer matrix, i.e., mesh, with embedded gelling powder, with a series of alcohol solution washes and water washes to remove residual solvent; Activating and gelling the dried gelling powder during the washing step, where the dried gelling powder absorbs water and transforms into a gel, which fills, exudes and encapsulates the microporous polymer matrix, i.e., mesh, structure; drying the gel containing the encapsulated microporous polymer matrix, i.e., mesh, into a storage stable structure and in a dry form; and hydrating the storage-stable structure in an aqueous solution.
[0008] The solvent-based polymer may be a solvent-based biocompatible polymer. The dried microporous polymer matrix, i.e., mesh, with embedded gelling powder may additionally be mechanically comminuted to produce degraded scaffold microgranules, or in other words degraded scaffold gelling granules, containing the gelling powder. The hydrating step may be a step of implanting the storage-stable construct in the patient. The method includes: hydrating a structure having a microporous polymer matrix with embedded dried gelling powder connected by a gel network (microgranular embedded gel) and forming an interconnected solid-gel suspension by hydrating degraded scaffold gelling granules suspended within the gel network; and injecting the interconnected solid-gel suspension by means of a syringe, the solid-gel suspension being fixed within the discrete units of the nano- and microporous biocompatible polymer particles prior to the washing step, forming a separate structure comprising a continuously connected hydrogel surrounding these units, said gel being microstructurally, i.e. physically, fixed within the nano- and microporous biocompatible polymer particles after the hydration step.
[0009] The present disclosure describes other 3D printed structures having one or more self-gelling components. The 3D printed structures include a polymer matrix, i.e., mesh, structure, that encapsulates or incorporates anhydrous washed absorbent dry gelling powder consisting of discrete dehydrated particles that are freeze-dried and configured to form a gel in an aqueous solution. The dry gelling powder can be configured to be fixed within the microstructure of the polymer matrix, i.e., mesh, structure, upon gelation. In other words, the dry gelling powder is embedded within the microstructure of the polymer matrix, i.e., mesh, and when the gelling powder is exposed to water and subsequently gels, the resulting gel is fixed at the location of the original dry gelling powder particles within the nano- and microporous non-gelling polymer microstructure. The gel not only encapsulates and surrounds the polymer microstructure, but also penetrates and is fixed within it. The self-gelling 3D printed structure may further include microparticles and / or nanoparticles configured to be embedded within the microporous polymer matrix, i.e., mesh, structure, by being encapsulated in a solid-gel suspension that is encapsulated or incorporated within the polymer matrix, i.e., mesh, structure, upon gelation. The polymer matrix, i.e., mesh, structure, may be a biocompatible polymer matrix, i.e., mesh, structure. In examples, the ink composition itself is not and does not include a gel.
[0010] The microparticles and / or nanoparticles can be embedded within a porous polymer matrix, i.e., mesh, as can the gelling powder. Upon hydration, the gelling powder turns into a gel and expands, filling and encapsulating the porous polymer matrix, i.e., mesh, as well as encapsulating the surrounding microparticles and / or nanoparticles. The length scale of the microparticles and / or nanoparticles is such that the expansion and swelling of the gel powder upon hydration actually moves / pushes the microparticles and / or nanoparticles through the porous polymer network. In one example, the nanoparticles are displaced by the hydrated gel, while the microparticles are not displaced or are not significantly displaced by the expanding gel.
[0011] The present disclosure describes other ink compositions for printing 3D printed structures. The ink composition includes a solvent-based polymer that encapsulates or incorporates anhydrous gelling powder in discreate particles, the gelling powder being configured to gel in an aqueous solution after extrusion. In other words, the gelling powder is extruded with the ink and does not gel until after extrusion or the 3D printed structure is formed. Since the gelling powder does not gel until it is exposed to an aqueous environment, the gelling powder is extruded with the ink and does not gel until after extrusion. The 3D printed structure can then be exposed to an aqueous solution and the gelling powder will gel. In other words, the ink containing the gelling powder does not gel during extrusion, after extrusion, or after the formation of the 3D printed structure until the 3D printed structure is exposed to an aqueous environment. The ink composition may further include microparticles and / or nanoparticles configured to be embedded within a microporous polymer matrix, i.e., a mesh, having a structure in which the gelling powder is embedded. The solvent-based polymer is a solvent-based biocompatible polymer. In examples, the ink composition is not and does not contain a gel. Further, in examples, the 3D printed structure is not and does not contain a gel. In examples, the dry gelling powder has an average particle size of less than 100 μm. In some examples, the dry gelling powder component is used in combination with one or more conductive materials, ceramic materials, metallic materials, drugs, synthetic chemistries, or bio-derived materials.
[0012] Also described is a method of forming a polymer having one or more self-gelling components, the method comprising: combining the solvent-based microporous polymer with the dried gelling powder to form an ink and extruding the ink to form a microporous polymer structure with embedded gelling powder; washing the gelling powder embedded structured microporous polymer with a non-aqueous solvent wash or anhydrous wash to prevent pre-gelation; drying the washed gelling powder embedded structured microporous polymer to form a dry, storage stable structure; Activating and gelling the gelling powder component of the dry, storage-stable structure by hydrating the dry, storage-stable structure in an aqueous solution, where gelling of the dried, gelling powder component absorbs water or a primary aqueous solution (e.g., including but not limited to water, blood, cell suspensions, biological plasma, drug-containing solutions, etc.), causing gelling and swelling of the microporous polymer matrix, i.e., mesh, component of the dry, storage-stable structure.
[0013] The solvent-based polymer may be a solvent-based biocompatible polymer. The dried microporous polymer matrix with gelling powder embedded structure, i.e. mesh, may additionally be mechanically comminuted to produce degraded scaffold gelling granules. The hydrating step may be implanting the storage-stable structure with gelling powder and / or degraded scaffold gelling granules in a patient. The implanting step of the dried storage-stable structure may be performed before the activating or gelling step. The degraded scaffold gelling granules may further be formed by mixing or combining separate degraded scaffold microgranules. For example, a quantity of hyaluronic acid self-gelling microgranules may be dry-mixed with a quantity of gelatin or collagen self-gelling microgranules, also in dry form. Hydration would be performed after dry mixing. This method may include: The method further comprises the steps of forming a gel suspension with embedded microgranules by hydrating the micro-scaffold particles (i.e. structures having microporous polymer with embedded gelling powder) containing gelling powder, and injecting the solid-gel suspension by a syringe, which forms another structure comprising a continuous hydrogel that is fixed within and surrounds the separate units of the nano- and microporous biocompatible polymer particles before the washing step, said gel being microstructurally, i.e. physically, fixed within the nano- and microporous biocompatible polymer particles after the hydration step.
[0014] In examples, microparticles and nanoparticles are embedded within the microporous polymer matrix. The nanoparticles can be or include metals, ceramics, drugs, RNA, DNA, bioactive factors, or other bio-relevant substances, and the microparticles can be or include metals, ceramics, drugs, RNA, DNA, bioactive factors, or other bio-relevant substances different from the nanoparticles. In one example, the nanoparticles are metals and the microparticles are ceramics, or vice versa. In some examples, the above method further includes embedding a dry, storage-stable material prior to the activating or gelling step.
[0015] The foregoing and other objects, features and advantages of these examples will become apparent from the following more particular description of specific examples that are illustrated in the accompanying drawings, in which like reference numerals represent like parts of the examples.
[0016] Reference is made to the accompanying drawings in which specific examples and further advantages of these examples are shown as will be explained in more detail in the following description. [Brief description of the drawings]
[0017] [Figure 1A]1 is an image of a product of the present disclosure where a gelling powder has been added to the product's 3D printing ink composition prior to molding, according to an example of the present disclosure, the product being shown in a state prior to activation or gelling. [Figure 1B] FIG. 11 is an image of a product of the present disclosure having a gelling powder added to a 3D printing ink composition according to one example of the present disclosure, which undergoes activation or gelation, such as a post-printing or post-processing rehydration process (after activation or gelation), to form a gel that exudes from, surrounds, and is microstructurally, i.e. physically, anchored (within the polymer matrix, i.e. mesh, scaffold) to a microporous polymer matrix, i.e., mesh, scaffold. [Figure 2A] FIG. 1 is a flow diagram of a self-gelling approach (referred to herein as Approach 1) for forming a biocompatible polymer matrix, i.e., mesh, that defines the structure of an object that is further encapsulated within a gel that is a product of an ink composition including a gelling powder, which is washed by a repeated series of alcohol solution washes and water washes performed after extrusion, according to an example of the present disclosure. Due to the highly absorbent nature of the gelling powder, after extrusion, the washing approach allows the gelling powder to absorb water and gel, resulting in a biocompatible polymer matrix, i.e., mesh, structure encapsulated within the gel. [Figure 2B] 2B shows product images corresponding to the steps of the flow diagram of FIG. 2A for the self-gelling approach (referred to herein as Approach 1). The representative product in the images is of the self-gelling approach forming a biocompatible polymer matrix, i.e. mesh, that defines the structure of the object that is further encapsulated within the gel, which is the product of an ink composition including a gelling powder that is washed by a repeated series of alcohol solution washes and water washes performed after extrusion according to one example of the present disclosure; due to the highly absorbent nature of the gelling powder, after extrusion, the washing approach allows the gelling powder to absorb water and gel, resulting in a biocompatible polymer matrix, i.e. mesh, structure encapsulated within the gel. [Figure 3A]FIG. 2 is a flow diagram of another approach (herein referred to as Approach 2) for forming a biocompatible polymer matrix, i.e., mesh, defining a structure of an object that is further encapsulated within a gel, which is a product of gelled powders constituting an ink composition, according to one example of the present disclosure, said product being washed with anhydrous washes performed in a fully or mainly (>50%) non-aqueous solvent, such as isopropanol, ethanol, or other alcohol-based solutions to prevent pre-gelation, to provide a lyophilized (freeze-dried) gelled powder that may then be relied upon in a product that may gel upon rehydration in a controlled environment to provide a biocompatible polymer matrix, i.e., mesh, structure, encapsulated within the gel. [Figure 3B] 3B shows product images corresponding to a step of the flow diagram of FIG. 3A (referred to herein as Approach 2). The representative product in the image shows the formation of a biocompatible polymer matrix, i.e. mesh, defining a structure of objects that are further encapsulated within a gel, a product of gelled powders constituting an ink composition, according to one example of the present disclosure, which is washed with anhydrous washes performed in a fully or mainly (>50%) non-aqueous solvent, such as isopropanol, ethanol, or other alcohol-based solutions to prevent pre-gelation, to provide a lyophilized (freeze-dried) gelled powder that may then be relied upon in a product that may gel upon rehydration in a controlled environment to provide a biocompatible polymer matrix, i.e. mesh, structure encapsulated within the gel. [Figure 4]Flow diagram of an additive approach (referred to herein as Approach 3) of dried gelling powder structures, i.e. gelling powder-containing structures, such as extruded fibers, that undergo additional processing (e.g. mechanical grinding) to produce degraded scaffold microgranules, i.e. degraded scaffold gelling granules. Such a population of degraded scaffold microgranules, i.e. degraded scaffold gelling granules, is storage stable in dry form, but can be hydrated (see below) to cause gelation of the powder contained within the polymer matrix of the particles to lubricate the particles and form an interconnected network of discrete microgranules connected by and suspended within a gel network, referred to herein as a solid-gel suspension, and syringe-injectable. Such hydrated materials can be 3D printed into further materials or structures (composed of discontinuous, separate units of nano- and microporous biocompatible polymer particles connected by a gel network characterized by microstructured anchoring "points" within each biocompatible polymer microparticle) according to one example of the present disclosure. [Figure 5A] Scanning electron micrograph image (left image) of the interior of a 3D printed fiber within a larger 3D printed scaffold composed of gelatin self-gelling powder in a porous matrix prior to activation / gelation (pre-hydration) according to an example of the present disclosure. [Figure 5B] Scanning electron micrograph image (right image) of the interior of 3D printed fibers within a larger 3D printed scaffold composed of gelatin self-gelling powder in a porous matrix after activation / gelation (after hydration) according to one example of the present disclosure, where the porous microscaffold 500 is labeled, the gelatin gel 510 is labeled, and the gelatin gel 520 anchored within the nano- and microporous polymer mesh is labeled. [Figure 6A]Scanning electron micrograph image of a cross section inside a 3D printed fiber within a larger 3D printed scaffold composed of calcium phosphate ceramic spheres and hyaluronic acid self-gelling powder in a porous matrix or mesh prior to activation or gelation (left image) according to one example of the present disclosure. [Figure 6B] Scanning electron micrograph image of a cross section inside a 3D printed fiber within a larger 3D printed scaffold composed of calcium phosphate ceramic spheres and hyaluronic acid self-gelling powder in a porous matrix or mesh after activation or gelation according to one example of the present disclosure (right image). [Figure 7A] Scanning electron micrograph (detail) images of individual degraded scaffold microgranules obtained by milling of a larger 3D printed construct. The granule on the left in FIG. 7A shows an individual degraded scaffold microgranule (non-self-gelling) according to one example of the present disclosure, specifically composed of a non-porous and microporous polylactide-co-glycolide matrix. [Figure 7B] Scanning electron micrograph (detail) images of individual degraded scaffold microgranules obtained by milling of a larger 3D printed construct. The granule on the right in FIG. 7B shows an individual degraded scaffold microgranule (pre-activation / pre-gelation) containing hyaluronic acid gelling powder according to one example of the present disclosure, specifically composed of dry hyaluronic acid powder embedded within a nano- and microporous PLG matrix. [Figure 8A] Photograph (top image) of a syringe containing a hydrated (saline) mixture of non-self-gelling degrading scaffold microgranules (about 33% by weight) and self-gelling hyaluronic acid degrading scaffold microgranules (about 65% by weight) prior to extrusion through a 22 Gauge (Ga) needle, according to an example of the present disclosure, which mixture can be extruded through a 22 Ga needle. [Figure 8B] A scanning electron micrograph image of extruded microgranules according to an example of the present disclosure (left image). [Figure 8C]Scanning electron micrograph images of discrete microgranules interlocking with each other and connected by exuded gel, according to an example of the present disclosure, where the gel 800 emanating from within the polymer matrix granules is labeled and the biocompatible polymer matrix microgranules 850 emanating from the degraded scaffold are labeled (right image). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The self-gelling materials and structures defined in the present invention in various embodiments offer improved performance over the limitations of existing gels, for example because: 1) the microstructural, i.e., physically, anchored properties help localize the gel and the entire printed or otherwise formed structure, giving the gel a structural form that allows it to be localized and even sutured in place in the body, reducing gel migration and increasing its residence time; 2) the underlying 3D printed structure helps contain and support the gel after implantation; and / or 3) the material containing the dried gelling powder and / or dried degraded scaffold gelling granules is storage stable, e.g., can be cut, clipped, compressed, delivered by cannula, etc., prior to hydration, allowing the material to be positioned and hydrated with the surrounding blood, medium, plasma, etc. upon implantation, greatly increasing the ability of the device to integrate and heal with the surrounding tissue. The constructs with one or more self-gelling components disclosed herein are distinct from pre-hydrated gel injectables, which are already hydrated and therefore much slower to absorb surrounding biological components. In addition, the underlying polymer mesh structure helps maintain implant morphology and localization better than polymer meshes with gel added prior to implantation, where the gel is not microstructurally, i.e. physically, anchored within the microstructure of the polymer network, but instead simply loosely encapsulates it. Figure 1A shows a material made from an ink containing gelling powder in a dry, storage-stable state prior to activation or gelling. Figure 1B shows an activated, self-gelling material made from an ink containing gelling powder.
[0019] In its simplest form, the present invention solves the problem of hydrogel localization for medical applications (making existing gels more effective). Specifically, a "self-gelling" structure is defined herein as a structure, scaffold, or material that can be implanted / introduced / placed in a wound or body as a dry structured object, or in the environment as an implant, and upon exposure to body moisture or introduction to the environment, at least a portion of which is activated to form a gel that encapsulates and anchors a defined microporous polymer structure therein. In other words, "self-gelling." The gelling powder within the polymer matrix, i.e., mesh, is "activated" by essentially absorbing water (and anything in the water, e.g., blood cells), sometimes up to five times its own weight or more. The absorption results in a very large volume change and effective transformation of the dry, solid gelled powder particles into an expandable, wet hydrogel that saturates the nano- and micropores of the polymer (i.e., the polyester matrix or mesh) and eventually seeps across the boundaries of the polymer components, encapsulating the polymer material and generally encapsulating the larger 3D printed construct.
[0020] In this "activated state," the morphology of the 3D printed polymer material remains in its original form (although it expands slightly as a result of gel expansion as the gel forms, pressing against the polymer pore walls from the inside out) and acts as a polymer reinforcement for the gel.
[0021] Three specific application areas used as examples demonstrate the advantages of the approach of the present disclosure as follows: Example 1: Biological joint (osteochondral) repair with 3D printed hyaluronic acid constructs with one or more self-gelling components. In this example, hyaluronic acid (HyAc) is a substance that is naturally present in cartilaginous connective tissue and is therefore frequently used to treat damaged or deteriorated joints (trauma, arthritis, side effects of surgery, etc.). For these treatments, HyAc is typically used as an injectable gel or added to an existing implant device and implanted. Although HyAc is compositionally suitable for treating joint diseases, HyAc gel injections have limited and short-lasting effectiveness because the HyAc gel migrates from the initial injection site as a result of normal biological movement. This migration also causes the HyAc gel to physically break down and not be properly incorporated or integrated into the surrounding tissue. This problem is slightly alleviated if the gel is injected into an existing porous structure and then this structure is implanted, but the gel will not be well integrated into the porous implant structure and will begin to migrate from the site with movement. In addition, both of these existing approaches require the gel to become a hydrated gel immediately prior to implantation, limiting the amount of surrounding blood and biological media that can be absorbed by the injectate or implant. In the present invention, the designer construct (of the required shape and form factor) can be deployed at the desired site by standard or minimally invasive or cannulation processes and sutured to the surrounding tissue, thereby fixing the construct in place, and the construct absorbs the surrounding blood, cells, etc., resulting in swelling and further fixing it in place. The resulting gel within the construct is microstructurally, i.e. physically, anchored to the polymer mesh network, helping to keep the gel localized even during movement, thus extending its residence time and therapeutic effect.
[0022] Example 2: Injectable gel to treat damaged tissue or organ (i.e., cardiac tissue after infarction). As with the previous example, many conditions result in superficial or subsurface damage to tissues and organs. One example is myocardial infarction, which results in necrotic cardiac tissue. Emerging methods to treat this include injecting hydrogels loaded with drugs, cells, etc. directly onto the damaged tissue. However, due to the superficial nature of the defect, as well as the dynamic nature of the organ, the gel will not remain localized for long periods of time, limiting its therapeutic potential. For example, a sheet of material with one or more self-gelling components can be delivered to the heart by cannula and secured (by surgical glue or thin sutures) at / around the site of injury. The implant will be in the form of a structure with self-gelling during this process, and the resulting gel will be anchored within the structurally highly porous polymeric microstructure of the structure, keeping the implant localized at the desired site.
[0023] Example 3: In cases where an injectable is still required (minimally invasive procedures where larger implants cannot be used), a microscaffold approach (approach 3 described below) can be used instead of directly injecting the hydrogel. Although not as effective at localizing the gel as larger structures would be, the presence of the microparticles and their integration with the exuded gel will help preserve the morphology and residence time of the injectate. One example is for treating subsurface spinal injuries, whereby injection of the microscaffold particles into the injury site results in a self-gelling (expanding) therapeutic filler that is somewhat anchored to the site due to the connection between the gel and the microporous structure of the polymer microparticles.
[0024] The embodiments of the present disclosure may be relied upon as a unique extension or improvement to the ink compositions and / or scaffold materials of U.S. Patent No. 10,584,254, entitled "INK COMPOSITIONS FOR THREE-DIMENSIONAL PRINTING AND METHODS OF FORMING OBJECTS USING THE INK COMPOSITIONS," filed November 14, 2016, which is incorporated herein by reference in its entirety (hereinafter referred to as the "'254 patent"). The '254 patent describes a 3D printable "ink" (which can be extruded in layers at room temperature without chemical or thermal reaction) formed from a series of solvents, biocompatible polymers, and particles / powders. This "ink" can be 3D printed into a variety of form factors and is also suitable for other manufacturing methods (e.g., fiber formation, textile, weaving, casting, etc.). While a basic ink composition approach may be relied upon from the compositions of the '254 patent discussed above, the present disclosure describes post-processable materials, processes, means of use, and / or features that are distinct from the basic ink compositions described in the '254 patent. Specifically, the present disclosure describes gelling powders and self-gelling techniques that remain localized and are structurally supported by the ink compositions and / or scaffolds of the '254 patent, as shown to be insufficient in the prior art. While the '254 patent is relied upon herein as an example of an ink composition and / or structure, or scaffold, it is understood that the self-gelling techniques and gelling powders of the present disclosure may be relied upon as an improvement to other ink compositions and / or structures, or scaffolds, as discussed below.
[0025] Powders and inks In the present example, the inks, such as those disclosed by the '254 patent, may contain one or more post-forming powders that are dry (essentially moisture-free), wettable, highly hygroscopic (water-absorbent) materials (hereinafter "gelling powders") that undergo substantial swelling when exposed to moisture. The gelling powders must not be substantially soluble or are insoluble in non-polar solvents, such as alcohol or dichloromethanes. When the intended use of the ink is for extrusion-based 3D printing, such as those disclosed by the '254 patent, the gelling powders preferably have an average particle size of less than 100 μm so that the material can be extruded and deposited from a fine tip nozzle.
[0026] The gelling powders can be synthetic (e.g., polyethylene glycol, polyethylene oxide, or variants thereof), natural (gelatin, cellulose, chitosan, alginates, "gummies", hyaluronic acid, other polysaccharides), zeolites, naturally derived materials (hyaluronic acid and the aforementioned materials derived from bacterial or fungal fermentation), synthetically derived natural materials (synthetically produced collagen), silicates, silicon-based polymers, or combinations thereof. In some instances, the gelling powder can hold a significant amount of water through HH interactions (hydrogen bonds) or electrostatic interactions. Significant can mean more than the dry mass of the gelling powder. For example, one gram of dry gelling powder should be able to hold at least one gram of water or other aqueous solution. The gelling powders may be chemically functionalized (with small molecules, drugs, proteins, peptides, nanoparticles, acidic groups, basic groups, etc.) prior to use in the ink synthesis, as long as the functionalization does not confer solubility in non-aqueous solvents such as alcohol or dichloromethane. The gelling powders can exhibit a wide range of average molecular weights, molecular numbers, polydispersities, etc. Molecular weights can range from 500 to 5,000,000 Daltons in most instances.
[0027] A typical ink relied upon for use in combination with the gelling powder is composed of a ternary solvent mixture of an evaporant (e.g., dichloromethane), a surfactant (e.g., 2-butoxyethanol), a plasticizer, and a polymer, which may be a non-biocompatible polymer such as, for example, one or more of polystyrene, polyvinyl alcohol, and the like. The polymer may additionally or alternatively be a biocompatible polymer such as, for example, one or more of poly(lactide-co-glycolide (PLG), polylactide (PLA), polycaprolactone, polyglycolide, and the like. The inks of the present disclosure may additionally or alternatively be used with cyclodextrin to adjust the solubility of the ink composition. The three solvent mixtures, and the polymers and more specifically the biocompatible polymers, may be generally the same as those previously described in the '254 patent. The polymer may be added to and dissolved in the evaporative agent (slowly dissolves under ambient conditions). In one specific example, 1 g of polymer is used per 2-10 g of evaporative agent. The amount of evaporative agent may be altered depending on the desired viscosity of the final ink. Surfactants and plasticizers are added to the evaporative agent / dissolved polymer. The amount of surfactant relative to the evaporative agent may vary depending on the desired final properties of the ink and the nature of the powder being used.
[0028] In the present disclosure, the ink is combined with or includes a gelling powder. The combination of gelling powder and ink is a single, integral material. In one example, the powder component comprises 50-80% by volume (vol.%) (solids, polymer+powder). All of the powder components of the resulting ink may be gelling powders, including multiple separate gelling powders, or the powder components may be comprised in part of gelling powders and in part of non-gelling powders that are compatible with the underlying ink composition (not soluble in dichloromethane or similar non-polar solvents). For example, the ink may contain 35% by volume hyaluronic acid (AKA: sodium hyaluronate-gelling powder) and 35% by volume bioceramic (e.g., calcium phosphates such as bioceramics). The ink-powder combination should be substantially free of water or other aqueous fluids. The ink will dry and solidify rapidly when exposed to air. The molecular weight of the gelling powder can range from 10,000 kDa to 10,000,000 kDa. In a specific example, the gelling powder is added last. The ink is physically mixed until homogeneous, at which point it is ready to be 3D printed by room temperature extrusion. The resulting 3D printed structure contains the polymer (present as nano- and micro-porous matrices in addition to the larger 3D printed macromorphs), the powder(s) (embedded within the porous polymer matrix), and residues of the three solvents (embedded within and on the surface of the porous polymer matrix).
[0029] In addition to the gelling powder, other powders may be added to the ink. For example, the ink may contain hyaluronic acid (HA) gelling powder and hydroxyapatite (HA) bioceramic to produce a final "HAHA" 3D printing material. The gelling powder component may turn into a gel and expand greatly when exposed to water, and the bioceramic particles (e.g., if they are larger than nanoscale) may remain within the polymer matrix.
[0030] In some examples, the powder component of the resulting ink may be composed of gelling powder and conductive materials such as graphite, graphene, carbon nanotubes, carbon black, micro- or nano-diamonds, which will impart electrical conductivity to the final fabricated structure. In some examples, the powder component may be composed of gelling powder and bio-derived materials such as collagen and tissue-specific decellularized extracellular matrix (e.g., muscle, cartilage, kidney, liver, ovary, skin, fat, etc.), which will impart additional biological properties to the final fabricated structure. In still other examples, the powder component may be composed of gelling powder and a combination of powders of the types mentioned above, or any powder compatible with the three-solvent system. Some example inks may contain synthetic, natural, hybrid, organic, or inorganic nanoparticles (<1 μm) in addition to the gelling powder. Gelling powder-containing inks are highly viscous but can flow under their own weight at 1 G. Viscosity can be adjusted by modifying the amount of evaporant solvent present in the formulation; more will result in a lower viscosity ink, and less will result in a higher viscosity ink.
[0031] As used herein, gelling powders are distinguished from gels. Gelling powders are highly absorbent solids in powder form. Highly absorbent powders become gels only when exposed to or mixed with an aqueous solution, as defined below. The difference between the present disclosure and conventional 3D printing inks that may rely on gelling powders is that the gelling powder in a conventional ink is mixed with an aqueous solution as part of the ink before the ink is 3D printed, extruded, or molded to form a hydrogel structure, scaffold, or product. Thus, the gelling powder of a conventional ink is actually a gel, i.e., in its gel form. In contrast, the gelling powder of the present disclosure remains as a gelling powder, i.e., a solid, in the ink and throughout the ink extrusion process due to the non-aqueous solvent-based nature of the ink composition. The gelling powder of the present disclosure does not become a gel until after 3D printing, extrusion, or molding is completed and after post-processing. The ink does not contain a gel. In other words, the gelling powder does not gel until post-processing involves a structure, scaffold, or product formed from the ink and the corresponding gelling aqueous composition as described in Approaches 1-3.
[0032] For processing, the biocompatible polymer is added to the evaporator and dissolved. Typically, 1 g of polymer is used per 2-10 g of evaporator (the amount of evaporator can be altered depending on the desired viscosity of the final ink). To the evaporator / dissolved polymer, a surfactant and plasticizer are added. The amount relative to the evaporator can vary depending on the desired final properties of the ink and the nature of the powders being used. The gelling powder and other desired powder(s) are added last, typically such that the gelling powder and powders make up 85% or less by volume of the total solids of the ink (amount of polymer + powder). In some instances, the gelling powder makes up 1-85% by volume of the total solids of the ink (amount of polymer + powder). In still other instances, the gelling powder makes up 50-85% by volume of the total solids of the ink (amount of polymer + powder). This is physically mixed until uniform, at which point it is ready to be 3D printed by simple room temperature extrusion.
[0033] 3D Printing and Molding The gelled powder-containing ink is 3D printed or otherwise molded using a process already described in the '254 patent. Briefly, the gelled powder-containing ink is extruded in layers at room temperature by a pneumatic, piston, or auger driven mechanism. Within milliseconds after extrusion from a fine nozzle (100-1000 μm), the gelled powder-containing ink solidifies and can support its own weight during deposition onto a substrate, while maintaining the gelled powder as a solid rather than a gel. The substrate can be any material, including a pre-deposited gelled powder-containing ink. Through this process, layers of the gelled powder-containing ink can be deposited to form a solid structure composed of fibers (or filaments). Other uses of the ink include extrusion and accumulation of fibers / filaments. The fibers are flexible and can be used as is or further processed by braiding, cabling, weaving, or other textile manufacturing methods. Other uses of the inks include casting onto or pouring into flat, textured, or volumetric molds. Regardless of the method of manufacture, the resulting gelled powder-containing structures must be washed to remove residual solvent. Additionally or alternatively, gelled powder-containing inks are also incompatible with any process requiring the addition of significant thermal energy, e.g., heating, melting, etc., as this may degrade the dried gelled powder material.
[0034] The resulting 3D printed structure is composed of the polymer (present as a nano- and microporous matrix, i.e., mesh, in addition to the larger 3D printed macromorphs), the powder(s) embedded within the porous polymer matrix, i.e., mesh, and residues of the three solvents embedded within and on the porous polymer matrix, i.e., mesh. As used herein, "embedded" or "embedded in / within" is defined as incorporated into the microstructure of the material or microstructurally, i.e., physically, anchored.
[0035] Solvent residues can be removed by alternating a series of alcohol solution washes with water washes, or through washing with alcohol solutions only. In the example of alternating a series of alcohol solution washes with water washes, activation and gelation of the gelling powder component will be initiated by exposure to water (or a mostly water solution) prior to the drying step. After drying, the structure can be rehydrated upon exposure to sufficient liquid. In the example of washing with alcohol solutions only, activation and gelation will not occur prior to the drying step. If pre-activation of the gelling powder is desired after drying, the gelling powder (embedded within the polymer component) will gel upon exposure to water (or a mostly water solution or liquid / water environment). In comparison, if activation / gelation prior to drying is to be avoided, washing can be done with a mostly alcohol solution.
[0036] Post 3D printing and processing Post-forming, gelled powder-containing structures, ie, structures formed from inks in which the gelled powder remains as a solid rather than a gel, must be washed and dried.
[0037] Approach 1 (see Figures 2A-B) As shown by the steps in FIG. 2A and the products shown by FIG. 2B corresponding to each step in FIG. 2A, the gelled powder structure can be washed by repeating a series of alcohol solution washes and water washes. The alcohol and water washes are performed to remove residual solvent (manufacturing residues) from the structure. Due to the highly absorbent nature of the gelled powder, this washing approach activates the gelled powder by absorbing water and gelling, thereby encapsulating and permeating the biocompatible polymer matrix, i.e., mesh, that defines the overall structure of the object. A drying step after washing places the material or structure of the object in a storage-stable form. As used herein, "storage-stable" is defined as dry, dehydrated, or dried to form a material that can be cut, clipped, compressed, delivered by cannula, etc., prior to hydration or further processing. In other words, a storage stable construct can be placed upon implantation and hydrated with surrounding blood, media, plasma, etc., greatly enhancing the device's ability to integrate and heal with surrounding tissue (as opposed to an injectable, pre-hydrated gel, which is much slower to absorb surrounding biological components because it is already hydrated). The final hydration step, outlined below by "Aqueous Composition for Gelling," provides for end-use processing of the object's material or structure.
[0038] Approach 2 (see Figures 3A to 3B) Due to the highly absorbent (aqueous) nature of the gelling powder material, washing can be done in a completely or primarily (>50%) non-aqueous solvent, such as isopropanol, ethanol, or other alcohol-based solutions, to prevent pre-gelation, if necessary, as shown by the steps in FIG. 3A and the products shown in FIG. 3B corresponding to the respective steps in FIG. 3A. In other words, the gelling powder structure is not washed using an aqueous or primarily aqueous solution (e.g., water) to prevent activation of the gelling powder, but instead is washed using a non-aqueous solvent. In contrast, if exposed to an aqueous or primarily aqueous solution, the structure will gel, as in approach 1 above. This approach represents a substantial modification to the ink composition of the '254 patent, where the structure would otherwise need to be exposed to water.
[0039] In either approach, the washing time and amount of washing medium will vary depending on the size and exposed surface area of the object being washed. Typically, the washing time ranges from 5 to 120 minutes. Multiple washing cycles may be used. Drying after washing may be done by any single means or combination of means. In one example, the gelled powder structure, i.e., the object containing gelled powder (hereinafter referred to as "gelled powder inclusion"), washed primarily with an alcohol solution, may be air-dried or dried with the assistance of airflow (fan, compressed air, etc.). In another example, the gelled powder structure, i.e., the gelled powder inclusion, washed primarily with an alcohol solution, may be lyophilized (freeze-dried). However, due to the high alcohol content, users must ensure that the freeze-drier used is capable of condensing (freezing) the solution used to wash the gelled powder structure, i.e., the gelled powder inclusion. In another example, the gelled powder structure, i.e., the gelled powder inclusion, washed with an alcohol solution, may be critical point dried using supercritical CO2 at the appropriate pressure and temperature. It is important that any object undergoing critical point drying is substantially free of water prior to critical point drying. The resulting dried gelled powder structure, i.e., gelled powder inclusion, should be shelf stable so long as it is typically stored in a moisture-free environment (desiccator, sealed packaging, etc.) at a temperature below 60°C. The resulting dried, gelled powder, or gelled powder inclusion, can be described as a composite of a biocompatible polymer and discrete particles of embedded gelled powder. The biocompatible polymer component is typically microporous and can be described as a disordered interconnected mesh network. Within the mesh network, the gelled powder particles are trapped, and the structure produced does not contain any gel or substantial amounts of water (e.g., the structure is a solid material rather than a gel or liquid). The gelled powder particles can then be activated or hydrated as outlined below by "Aqueous Compositions for Gelling".
[0040] With respect to approaches 1-2 above, the dry gelling powders may be prepared by subjecting the dry gelling powders to the processes disclosed in U.S. Patent No. 9,327,448, filed August 1, 2014, entitled "METHODS FOR FABRICATING THREE-DIMENSIONAL METALLIC OBJECTS VIA ADDITIVE MANUFACTURING USING METAL OXIDE PASTES"; U.S. Patent No. 10,236,528, filed July 18, 2016, entitled "THREE DIMENSIONAL EXTRUSION PRINTED ELECTROCHEMICAL DEVICES"; U.S. Patent No. 10,350,329, filed October 15, 2015, entitled "GRAPHENE-BASED INK COMPOSITIONS FOR THREE-DIMENSIONAL PRINTING APPLICATIONS"; and U.S. Patent No. 10,350,329, filed April 7, 2016, entitled "INK COMPOSITIONS FOR FABRICATING OBJECTS FROM REGOLITHS AND No. 10,793,733, entitled "METHODS OF FORMING THE OBJECTS"; U.S. Patent Application Publication No. 2019 / 0343989A1, entitled "SURGICALLY-FRIENDLY TISSUE PAPERS FROM ORGAN-SPECIFIC DECELLULARIZED EXTRACELLULAR MATRICES," filed May 16, 2019; and U.S. Patent Application Publication No. 2020 / 0353129A1, entitled "WATER-SOLUBLE SALT PARTICLE CONTAINING COMPOSITIONS AND POROUS MATERIALS MADE THEREFROM," filed April 29, 2020. All of the above patent documents are incorporated herein by reference in their entirety.
[0041] Approach 3 (see Figure 4) Dried gelling powder structures, i.e. gelling powder-containing structures, such as extruded fibers, can be subjected to additional processing to produce degraded scaffold microgranules containing gelling powder, in other words degraded scaffold gelling granules. Specifically, dried gelling powder structures, i.e. gelling powder-containing structures, can be mechanically pulverized (cutting mill) and sieved to produce powders with individual particle compositions and microstructures representative of larger 3D printed or otherwise formed gelling powder structures, i.e. gelling powder-containing structures. Such a population of degraded scaffold microgranule powders containing gelling powders is storage stable in dry form, but can be hydrated (see below) to produce gelling of the powder contained within the polymer matrix of the particles to lubricate the particles and form an interconnected network of discrete microgranules connected by and suspended within the gel network, which can be extruded by a syringe. Such hydrated materials can be 3D printed into further materials / structures (composed of discontinuous separate units of nano- and microporous biocompatible polymer particles connected by a gel network characterized by microstructured anchoring "points" within each biocompatible polymer microparticle). The term "degraded scaffold gelling granules" refers to the product obtained from grinding, as defined herein, not prior to grinding. In other words, the 3D printed, extruded, or otherwise formed product is additionally ground to produce a powder, with each powder particle having a composition and microstructure representative of the material prior to grinding. Degraded scaffold gelling granules are those structures formed from those powders obtained from the milled, extruded, or otherwise formed product. By grinding a large amount of material, a powder is produced from that material, with each powder particle being essentially a smaller version of that larger structure that was milled. Thus, each particle contains a composite of gelling powder, polymer, and any other powders that may have been present in the original material or ink. In addition, the milled powder may also be sieved and screened, if necessary, to obtain a particular size range. The size of the microgranules is typically 20 μm or larger.In one particular example, for cell delivery and tissue repair applications, it may be important for the microgranules to be several times larger than the majority of the cells that are directly adjacent or attached to them. This size difference facilitates the interaction of individual cells with individual microgranules in a manner similar to how individual cells interact with much larger structures that are composed of the same material and defined by the same microstructure as the microgranules.
[0042] Approach 3 is further illustrated by Figure 4. In Figure 4, a 3D printed construct comprising a porous polymer matrix, i.e., mesh, dried gelling powder embedded within the structure, formed by either approach 1 or 2 above (step 1 in Figure 4), is mechanically crushed to form storage-stable degraded scaffold gelling granules representative of the components of the original larger construct (step 2 in Figure 4). The mechanically crushed degraded scaffold gelling granules can be combined with an aqueous solution (e.g., blood, water, etc.), thereby activating / gelling the gelling powder components of the degraded scaffold gelling granules to form an activated / gelled scaffold suspension of degraded scaffold gelling granules (step 3 in Figure 4). The microgranule particles of the scaffold suspension of degraded scaffold gelling granules gel into a solidified, yet flowable, gel-particle suspension. This suspension can be loaded into a syringe and injected into or onto a site, such as a tissue, organ, or wound site (step 4 in Figure 4). Therefore, the degraded scaffold gelling granules can be further utilized as gelling powders in either approach 1 and 2.
[0043] As used herein in light of the above approaches, the washed structure is dried to obtain its "storage stable" state. Drying can be done by any number of methods, including air drying (with or without assistance such as a fan), critical point drying, freeze drying. The dried structure may consist of, consist of, or consist essentially of nano- and microporous polymeric matrices, i.e. meshes, in which gelling powders and / or degraded scaffold gelling granules (and other powders, if added) are embedded. The dried structure may be flexible and can be cut with scissors, razor blades, or equivalent sharp tools. The dried structure may also be capable of holding sutures or threads. The dried structure, if thin (in a sheet or membrane-like form), may also be compressed and forced into a cannula.
[0044] As used herein in light of the above approach, upon exposure to sufficient water, the gelling powder and / or degraded scaffold granules within the polymer matrix, i.e., mesh, "activate" and essentially soak up more than five times their own weight in water (and whatever is in the water, i.e., blood). The absorption results in a very large volume change and effective transformation of the dry, solid gelling powder particles into an expansive, wet hydrogel that saturates the nano- and micro-pores of the polymer (i.e., polyester) matrix, i.e., mesh, and eventually seeps out beyond the boundaries of the polymer components, encapsulating the polymeric material and generally encapsulating the larger 3D printed construct.
[0045] Aqueous Composition for Gelling Washed and dried structures containing gelling powders can exude "microstructurally fixed" or "physically fixed" gels when exposed to aqueous liquids, as shown by Figures 2A, 2B, 3A, and 3B. Essentially, the separate dried gelling powders and / or degraded scaffold gelling granules within the biocompatible polymer matrix, i.e., mesh, absorb water (and anything in the water) and begin to swell as they transform into a hydrogel (a predominantly water-containing material with a small amount of interconnected solid polymer network, where "predominantly" is defined as >50% by volume). This process is referred to herein as "activation" of the gelling powders and / or degraded scaffold gelling granules. This expansion creates pressure against the surrounding biocompatible polymer matrix, i.e., mesh, network, causing the now interconnected gel network to exude or be expelled from the still solid and highly porous biocompatible polymer network. As a result of the pressure of the expanding gel against the surrounding biocompatible polymer, solid mesh network, the mesh network expands, resulting in a macroscopic expansion of the fabricated object (typically 0.5-20% linear expansion in all directions). The gel volume increases to such an extent that, as a result of exposure to an aqueous solution, the gel network seeps beyond the boundaries / radius of the printed or otherwise formed biocompatible polymer mesh network, resulting in a structure that can be described as a highly porous but solid polymer mesh network embedded within the gel. Importantly, not only is the polymer mesh network embedded within the gel, but the gel is also embedded within the polymer mesh network (e.g., nanopores and micropores of the polymer network). This has important implications for properties and uses, since the gel is microstructurally, i.e., physically, anchored to / within the structurally porous biocompatible polymer component. Upon activation, post-processing transforms the gelling powder and / or degraded scaffold gelling granules into a gel that is exuded from within the material or structure (i.e., inside-out gelation).This is in contrast to adding gel to an existing surface as taught by US Patent Application Publication No. 2019 / 0060516, which adds gel to an existing surface, or gluing the gel (i.e., from the outside in). Gels that are independent of the structure have been found to shear and move or move. In contrast, the activated gels of the present disclosure that are anchored to a structure, scaffold, or product, as described herein, do not shear or move, or do not shear or move to such an extent. In other words, gels that exude from within a material or structure, as opposed to gels that are added to an existing material or structure, have anchoring points (such that the gel is attached or anchored within the more substantial nanoporous and microporous polymer matrix, i.e., mesh) such that when a shear force is applied to the gel exuding from the nanoporous and microporous polymer matrix, i.e., mesh, and then released, the gel returns to its original position. This limits gel movement and increases gel residence time when the gel is implanted in this 3D printed form compared to gel that is simply injected or added later to an existing structure (3D printed or not).
[0046] In another example of the present disclosure, the inks containing powder components may be a combination of one or more of gelling powders, degraded scaffold gelling granules, microscale (1-100 micrometers on average) non-gelling powder particles, and nanoscale (0.001-0.999 micrometers on average) non-gelling particles. Microparticles are any material that is substantially insoluble or insoluble in dichloromethane, including but not limited to ceramics, metals, alloys, covalently bonded solids, biological particles (extracellular matrix, collagen, proteins), or modified particles thereof. Modifications may include but are not limited to surface functionalization, coatings, and encapsulation with other materials. Nanoscale particles may include materials in the same category as microscale particles, in addition to proteins, drugs, peptides, and bioactive factors.
[0047] The constructs containing the dried gelling powder and / or degraded scaffold gelling granules can be hydrated / gelled with any number of aqueous solutions, including but not limited to the following: water, saline, blood, plasma, purified blood products (platelet rich plasma), and aqueous solutions containing cells, drugs, proteins, peptides, cell or tissue culture media, small molecules, nanoparticles, antibiotics, antifungals, etc. The rate of hydration and extent of gelling (i.e., how much gel is exuded from the polymer network) depends on several factors, including but not limited to the relative volume percent of the gelling powder and / or degraded scaffold gelling granules in the construct (relative to other powders and polymeric components), the molecular weight and polydispersity of the gelling powder and / or degraded scaffold gelling granule material, and the aqueous solution used for gelling. In this way, gelation can be controlled to adjust the gel "radius" around biocompatible polymer fibers or larger structures (i.e., small amounts of gelling powder and / or degraded scaffold gelling granules can result in a gelling radius around the printed fiber of approximately 10-100 μm, or even extending to several millimeters).
[0048] Structures containing dried gelling powders and / or degraded scaffold gelling granules are typically flexible and can be elastically and plastically deformed (bent, folded, etc.) to shape, cut, stamped, and otherwise trimmed, depending on the form factor. These processes can also be performed after the structure is hydrated and gelled.
[0049] The hydrated, gelled structure can optionally be lyophilized (freeze-dried) to obtain a water-free structure defined by the original biocompatible polymer mesh network embedded within the dried gel network (and also within the polymer mesh microstructure).
[0050] Although the present invention has been described with reference to examples of the present invention, it is to be understood that such description is for illustrative purposes only and should not be construed as limiting the scope of the examples claimed. Thus, the scope and content of the examples should be defined only by the language of the claims that follow. Furthermore, it is understood that the features of any example discussed herein may be combined with one or more features of any one or more examples otherwise discussed or contemplated herein, unless otherwise indicated.
Claims
1. 1. A 3D printed structure having one or more self-gelling components, comprising: 3D printed structures are comprising a dry gelling powder embedded within a porous polymer matrix structure; A structure, wherein the gelling powder is configured to form a gel when contacted with an aqueous solution that causes the gelling powder to gel.
2. 10. The structure of claim 1, further comprising microparticles and nanoparticles embedded within the porous polymer matrix structure, the microparticles and nanoparticles being one or more of a conductive material, a ceramic material, a metallic material, and a biomaterial.
3. The structure described in claim 1, wherein the polymer matrix structure comprises a biocompatible polymer.
4. The structure of claim 3 , wherein the gel is physically anchored within the microstructure of a biocompatible polymer matrix structure.
5. 1. An ink composition for printing a 3D printed structure having one or more self-gelling components, the ink composition comprising: Solvent-based polymer extrudates, The solvent-based polymer extrudate contains and maintains a dry gelling powder encapsulated or incorporated within the polymer, is washed in a dried alcohol and water wash after extrusion, remains in a storage stable, dry form when dried after extrusion, and is configured to gel when hydrated in an aqueous solution after extrusion.
6. The ink composition of claim 5 , wherein the ink composition is not a gel and is gel-free.
7. The ink composition of claim 5 , wherein the dry gelling powder has an average particle size of less than 100 μm.
8. 6. The ink composition of claim 5, wherein the solvent-based polymer extrudate has suspended therein additional powder components comprising one or more of nanoscale and microscale materials, the nanoscale and microscale materials being one or more of conductive materials, ceramic materials, metallic materials, and bio-derived materials.
9. 1. An ink composition for printing a 3D printed structure having one or more self-gelling components, the ink composition comprising:
1. An ink composition comprising a solvent-based polymer having encapsulated or embedded therein a freeze-dried, discrete dry particle, water-free washed, absorbent, dry gelling powder, the gelling powder being configured to gel in an aqueous solution after extrusion.
10. 10. The ink composition of claim 9, further comprising microparticles and nanoparticles configured to be embedded within a porous polymer matrix structure formed from said solvent-based polymer by being encapsulated in a solid-gel suspension that is encapsulated or incorporated within the polymer matrix structure upon gelation.
11. The ink composition of claim 9, wherein the solvent-based polymer is a solvent-based biocompatible polymer.
12. The ink composition of claim 9 , wherein the ink composition is not a gel and is gel-free.
13. The ink composition of claim 9, wherein the dry gelling powder has an average particle size of less than 100 μm.
14. The ink composition of claim 9 , wherein one or more powdered components of a conductive material or a bio-based material are additionally encapsulated or incorporated into the solvent-based polymer.